2019
DOI: 10.1080/21691401.2019.1649273
|View full text |Cite|
|
Sign up to set email alerts
|

RETRACTED ARTICLE: The circular RNA circ-ITCH acts as a tumour suppressor in osteosarcoma via regulating miR-22

Abstract: Background: Osteosarcoma (OS) is the most prevailing primary bone tumour and the third prevalent tumour in children and adolescents. Despite advanced treatments, the survival rate of OS has not been effectively improved. Here, we intended to investigate the functional impacts of circ-ITCH on OS. Methods: Circ-ITCH expression in OS tissues and cells was evaluated utilizing qRT-PCR. Viability and proliferation of MG63 and Saos-2 cells were determined by utilizing CCK-8 assay and BrdU assay. Transwell assay was u… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
34
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 44 publications
(34 citation statements)
references
References 45 publications
0
34
0
Order By: Relevance
“…Studies have confirmed that circRNAs, as miRNA sponges, competitively bind miRNAs and affect their activity and the expression of their downstream target genes [90,[108][109][110]. MiRNA regulation by circRNAs has been identified in some cancers [111][112][113][114][115]. Moreover, miRNAs have been shown to regulate m6A modifications [40,41].…”
Section: Regulation Of M6a Modifications By Noncoding Rnasmentioning
confidence: 95%
“…Studies have confirmed that circRNAs, as miRNA sponges, competitively bind miRNAs and affect their activity and the expression of their downstream target genes [90,[108][109][110]. MiRNA regulation by circRNAs has been identified in some cancers [111][112][113][114][115]. Moreover, miRNAs have been shown to regulate m6A modifications [40,41].…”
Section: Regulation Of M6a Modifications By Noncoding Rnasmentioning
confidence: 95%
“…However, another study carried out by Ren et al (74) stated the opposite result-that circ-ITCH had lower expression in OSA cells and was identified in clinical human OSA and para-tumor tissues. Their data showed that overexpression of circ-ITCH led to reduced SP-1 expression via PTEN/phosphoinositide 3-kinase (PI3K)/AKT pathways, which in turn suppressed proliferation, migration, and invasion by downregulating miR-22 (74). This is in concert with the conclusion that circ-ITCH might serve as an anti-oncogene via sponging multiple oncogenic miRNAs in multiple tumors, including ovarian cancer, prostate cancer, melanoma, gastric cancer, glioma, breast cancer, bladder cancer, papillary thyroid cancer, lung cancer, hepatocellular carcinoma, esophageal squamous cell carcinoma, and colorectal cancer (91,92).…”
Section: Osteosarcoma-related Circrna In Other Cancersmentioning
confidence: 94%
“…Further mechanistic studies revealed that circ-ITCH could promote the growth, migration, and invasion of OSA cells and even enhance epidermal growth factor receptor expression by reducing levels of miR-7 (30). However, another study carried out by Ren et al (74) stated the opposite result-that circ-ITCH had lower expression in OSA cells and was identified in clinical human OSA and para-tumor tissues. Their data showed that overexpression of circ-ITCH led to reduced SP-1 expression via PTEN/phosphoinositide 3-kinase (PI3K)/AKT pathways, which in turn suppressed proliferation, migration, and invasion by downregulating miR-22 (74).…”
Section: Osteosarcoma-related Circrna In Other Cancersmentioning
confidence: 99%
“…However, further research demonstrated that circRNAs are a distinct type of RNA molecule with modulatory effects on cellular events [ 143 , 144 , 145 , 146 ]. In the case of PTEN signaling, different experiments have shown that circRNAs are able to act as upstream mediators of the PTEN signaling pathway in cancer cells [ 147 , 148 , 149 ]. This section is devoted to investigating the role of circRNAs in the regulation of PTEN in GC cells.…”
Section: Pten and Gastric Cancermentioning
confidence: 99%